Quail Carcass Performance Using Additional Feed Combination Of Noni Leaf Flour And Black Cumin Flour - Nur, Khaeriyah; Abdullahi, Alima Bachtiar (Universitas Airlangga, 2024)
Background: Digestive disorders can attack quail and will have an impact on reducing their productivity, such as live weight, abdominal fat weight, and decreased carcass performance. Purpose: Providing additional feed from herbal plants in the form of noni flour and black cumin flour can overcome digestive system problems because they contain active substances that are useful as feed supplements, anti-inflammatory, anti-bacterial and others for the livestock's body. Method: The research design was a completely randomized design (CRD) with 4 treatments and 4 replications, each replication consisting of 6 quail. Feed treatments were P0: commercial feed (control), P1 = commercial feed + 1% black cumin flour + 3% noni leaf meal, P2 = commercial feed + 2% black cumin flour + 2% noni leaf meal, P3 = commercial feed + black cumin flour 3% + noni leaf flour 1%. The data was then analyzed using analysis of variance (ANOVA). Results: The results showed that the treatment given had a significant effect on the percentage of quail carcass weight. The P3 treatment was significantly higher than the other treatments, whereas the P2 treatment was the lowest compared to the other treatments, while the P0 and P1 treatments were not significantly different. Other parameters did not have a significant effect on the percentage of quail abdominal fat, pH, percentage of water holding capacity, and percentage of cooking loss of quail meat. Conclusion: In conclusion, the treatment had a significant effect on the percentage of quail carcass weight, while it had no significant effect on the percentage of quail abdominal fat, pH, percentage of water holding capacity, and percentage of cooking loss of quail meat.